2020
DOI: 10.3390/medicines7040021
|View full text |Cite
|
Sign up to set email alerts
|

Limited Utility of Serology and Heterophile Test in the Early Diagnosis of Epstein–Barr Virus Mononucleosis in a Child after Renal Transplantation

Abstract: Background: Epstein–Barr virus (EBV) infection is associated with significant morbidity and mortality in renal transplant (RT) recipients. The spectrum of illness ranges from infectious mononucleosis (IM) to post-transplant lymphoproliferative disorder (PTLD). In association with clinical signs and symptoms, virus-specific serology and heterophile antibody tests are widely used in confirming the diagnosis of IM in the general population. However, these tests may have a limited role in immunosuppressed RT recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Low-affinity EBV-CA IgG can be detected at the early stage of infection, but its level gradually decreases as the infection progresses; peripheral blood EBV-DNA generally starts to decline rapidly after 2 weeks of EBV infection and may not be detectable after fever reduction, but EBV-CA IgM levels gradually increase instead. 27 Recently, in a study reported for timely assessment and management. 27 The current study still has some limitations.…”
Section: Comparison Of Ebv Testing Results By Immunofluorescence and ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Low-affinity EBV-CA IgG can be detected at the early stage of infection, but its level gradually decreases as the infection progresses; peripheral blood EBV-DNA generally starts to decline rapidly after 2 weeks of EBV infection and may not be detectable after fever reduction, but EBV-CA IgM levels gradually increase instead. 27 Recently, in a study reported for timely assessment and management. 27 The current study still has some limitations.…”
Section: Comparison Of Ebv Testing Results By Immunofluorescence and ...mentioning
confidence: 99%
“…27 Recently, in a study reported for timely assessment and management. 27 The current study still has some limitations. First, the number of EBV-IM cases was relatively small.…”
Section: Comparison Of Ebv Testing Results By Immunofluorescence and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…They were subjected to pre-and posttransplantation evaluation as follows: I) Pretransplant evaluations: age, sex, previous blood transfusion, pretransplant hemodialysis, associated comorbidities as diabetes mellitus, the degree of matching between recipient and donor, and history of CMV and HCV infections. ,and classified according to their DU value as negative (<9 DU), grey zone (9)(10)(11), or positive (⩾11).…”
Section: Methodsmentioning
confidence: 99%